Efektivitas penurunan jumlah angka kuman alat makan dan efisiensi biaya yang digunakan pada metode pencucian alat makan di Rumah Sakit Kota Surakarta - Annisa Andriyani; I Made Alit Gunawan; Joko Susilo (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2009)
Background : Proper process of dishwashing has an important role in the prevention of disease transmission because unclean dishes that contain microorganism can transmit diseases through foods. Therefore, the process of dishwashing has to fulfill the standard of health. Currently, there are three methods of dishwashing in the hospital; electronic dishwashing, three compartment sink (TCS), and conventional method. They have the same purpose, i.e. cleaning dishes. To find out effectiveness and efficiency of those three methods, it is necessary to know the germ rate and cost spent. Objective : To identify the effectiveness of germ rate reduction and cost efficiency of electronic dishwashing, TCS, and conventional method of dishwashing at hospitals in Surakarta Municipality. Method : This experiment used randomized design trial. Populations were all dishes at hospitals of Surakarta Municipality with certain criteria. Hospitals that fulfilled the criteria were Dr. Moewardi Hospital, Prof. Dr. R. Soeharso Orthopedic Hospital, and Banjarsari Hospital. There were six items of samples consisting of two plates, two drinking glasses, and two spoons. The number of experiment units in the study were 3 experiments x 3 times repeating x 6 items of dishes x 2 evaluations totaling 108 units of experiment. Analysis used t-test, ANOVA, and cost effectiveness.Result : Washing process used electronic dishwashing, TCS, and simple method could reduce the different numbers of germs, those amounted to 84 colony/cm2, 1,276.38 colony/cm2, and 321.27 colony/cm2, respectively. TCS was the most effective and efficient method in reducing the number of germ. The cost only Rp 1,00 to reduce 15.56 colony/cm2 using TCS method. Conclusion : There were different reductions of germ rate after dishwashing used electronic dishwashing, TCS, and conventional methods. Among them, TCS was the most effective and efficient method in reducing germ rate.